The Influence of Job Satisfaction on Organizational Citizenship Behavior through Mediating Resilience in Millennial Workers - Muchtadin, Muchtadin (Social Sciences Insights Journal, 2023)
Organizational citizenship behavior (OCB) is one of the important aspects that the millennial generation needs to have because it is related to organizational effectiveness. This research is aimed at finding out the magnitude of the influence that job satisfaction has on OCB through the mediation of resilience. Respondents were 100 millennial workers in Indonesia where the sample was selected using convenience sampling. This research is quantitative cause and effect using the PLS SEM data analysis method. Data collection was carried out using a Google form which was distributed via various social media such as WhatsApp, LinkedIn and Facebook. The research results found that job satisfaction had a significant positive effect on resilience. Resilience also has a significant positive effect on OCB. Job satisfaction has no direct effect on OCB. Resilience fully mediates the effect of job satisfaction on OCB. This research contributes to increasing OCB through increasing job satisfaction and resilience in millennial workers in Indonesia.